Synthesis, spectroscopic, electrochemical and spectroelectrochemical properties of metal free, manganese, and cobalt phthalocyanines bearing peripherally octakis-[4-(thiophen-3-yl)-phenoxy] substituents - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Metal free (2), manganese (3). and cobalt (4) phthalocyanines, which are octa-substituted at the peripheral positions with [4-(thiophen-3-yl)-phenoxy] moieties, were synthesized and electrochemical properties were reported for the first time. The complexes were characterized by elemental analysis, IR,H-1 NMR, mass spectroscopy, and electronic spectroscopies. Electrochemical and spectroelectrochemical measurements exhibit that incorporation of the redox active metal ions, Co-II and (MnOAc)-O-III, into the phthalocyanine core extends the redox richness of the Pc ring with the reversible metal-based reduction and oxidation couples in addition to the common Pc ring-based electron transfer processes. Presence of molecular oxygen in the electrolyte system causes to form pi-oxo MnPc complexes, which alter the voltammetric and spectroelectrochemical responses of the complex. An in situ electrocolorimetric method has been applied to investigate the color of the electro-generated anionic and cationic forms of the complexes for possible electrochromatic applications. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanines; Manganese; Cobalt; Electrochemistry; Spectroelectrochemistry; Electrocolorimetry; IN-SITU; COMPLEXES; BEHAVIOR; REDUCTION; CHEMISTRY; ZINC(II); NICKEL; FILMS